Effectiveness of Mobile Health Interventions to Improve Medication Adherence Among Hypertensive Patients in Developing Countries: A Systematic Review - Nur Arifah Astri; Rifky Octavia Pradipta; Abu Bakar (Universitas Muhammadiyah Semarang, 2026)
Hypertension often occurs in developing countries; limited availability of information about hypertension can lead to increased prevalence, low detection rates, and less than optimal prevention and control, especially in medication adherence. Articles were searched using the PRISMA framework with a search period of November 2025 to December 2025. Articles retrieved were from the last 5 years with a randomized trial (RCT) method, descriptive, and quasi-experimental studies with the keywords mobile health, telemedicine, telehealth, MHealth, medication adherence, and hypertension. Based on inclusion and exclusion criteria in the analysis of 7 articles from various countries that have been published and meet the criteria. Interventions provided were in the form of SMS to applications created by a team of experts. Mobile health (mHealth)-based interventions, both through SMS and simple applications, are effective in increasing medication adherence because they are easily accessible, cost-effective, and able to overcome the problem of forgetting and limited health literacy.